Identification of Arl13b GTPase-activating proteins towards the impairment of tumor progression - Ferreira, Inês Margarida Castro (2018)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2018